PNPLA3 is the dominant SNP linked to liver disease severity at time of first referral to a tertiary center. Issue 1 (January 2022) - Balcar, Lorenz; Semmler, Georg; Oberkofler, Hannes; Zandanell, Stephan; Strasser, Michael; Datz, Leonora; Niederseer, David; Feldman, Alexandra; Stickel, Felix; Datz, Christian; Paulweber, Bernhard; Aigner, Elmar
Abstract: Background: Single nucleotide polymorphisms (SNPs) in genes including PNPLA3, TM6SF2, HSD17B13 and SERPINA1 have been identified as risk modifiers of progression in chronic liver disease (CLD). However, it is unclear whether genotyping for these risk variants is useful in clinical routine. Methods: Liver disease severity was assessed by liver stiffness measurement (LSM) and by presence of clinical manifestations of advanced-chronic liver disease (ACLD) in 779 consecutive CLD patients at the time of referral to a tertiary center. The associations of risk variants with CLD severity were calculated individually and in a combined model using a polygenic risk-score. Results: Non-alcoholic fatty liver disease (NAFLD) was the most common etiology ( n = 511, 65.6%), and ACLD was present in 217 (27.9%) patients. The PNPLA3 - G -allele remained independently associated with higher LSM (adjusted-B: 2.508 [95%CI: 0.887–4.130], P = 0.002) or the presence of ACLD (aOR: 1.562 [95%CI: 1.097–2.226], P = 0.013). SERPINA1 - Z -allele was also independently associated with LSM (adjusted-B: 4.558 [95%CI: 1.182–7.934], P = 0.008), while the other risk alleles did not attain statistical significance. Combining these risk alleles into a polygenic risk-score was significantly associated with LSM (adjusted-B: 0.948 [95%CI: 0.153–1.743], P = 0.020). Conclusion: PNPLA3 risk-variants are linked to liver disease severity at the time of first referral to an outpatient hepatology clinic .